Embodied Concepts and Mental Health. Issue 2 (13th March 2018) - Varga, Somogy
Abstract: Often drawing on the phenomenological tradition, a number of philosophers and cognitive scientists working in the field of "embodied cognition" subscribe to the general view that cognition is grounded in aspects of its sensorimotor embodiment and should be comprehended as the result of a dynamic interaction of nonneural and neural processes. After a brief introduction, the paper critically engages Lakoff and Johnson's "conceptual metaphor theory" (CMT), and provides a review of recent empirical evidence that appears to support it. Subsequently, the paper underscores some of the limitations of CMT, points to some philosophical problems that require further attention, and explores possible implications for understanding and treating of mental disorders.